Electrically, Chemically, and Photonically Powered Torsional and Tensile Actuation of Hybrid Carbon Nanotube Yarn Muscles - Lima, Marcio D.; Li, Na; de Andrade, Monica Jung; Fang, Shaoli; Oh, Jiyoung; Spinks, Geoffrey M.; Kozlov, Mikhail E.; Haines, Carter S.; Suh, Dongseok; Foroughi, Javad; Kim, Seon Jeong; Chen, Yongsheng; et al. (Amer Assoc Advancement Science, 2012)
Artificial muscles are of practical interest, but few types have been commercially exploited. Typical problems include slow response, low strain and force generation, short cycle life, use of electrolytes, and low energy efficiency. We have designed guest-filled, twist-spun carbon nanotube yarns as electrolyte-free muscles that provide fast, high-force, large-stroke torsional and tensile actuation. More than a million torsional and tensile actuation cycles are demonstrated, wherein a muscle spins a rotor at an average 11,500 revolutions/minute or delivers 3% tensile contraction at 1200 cycles/minute. Electrical, chemical, or photonic excitation of hybrid yarns changes guest dimensions and generates torsional rotation and contraction of the yarn host. Demonstrations include torsional motors, contractile muscles, and sensors that capture the energy of the sensing process to mechanically actuate.